Corruption in Perspective of Social Psychology and Psychology Cognitive Theory - Iing Saefudin, (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to explore corruption viewed from the perspective of social and cognitive psychology, that a variety of acts of deviant behavior, both caused by the background personality of people who do deviations and social situations that have the power to cause various acts of deviation. This paper uses a literature study approach. Data collection in this study, use study results, literature and mass media. These studies show that corruption and the crime of corruption is a phased development process based on social-psychological theory and cognitive psychology theory that explains why a person behaves in a distorted manner and ignores norms and mainstream truths that are not linear with the social psychology of the collective beliefs of society that uphold the value of truth namely the psychological effect of the asymmetry of power and self-interest becomes a driving force for someone to act corruptively.